KURIKULUM BERBASIS CINTA: PERSPEKTIF HADIS NABI - Ali Mohtarom; Syaifullah (Fakultas Agama Islam, 2026)
This study aims to integrate the Love-Based Curriculum (KBC) concept, initiated by the Indonesian Ministry of Religious Affairs, with the perspective of the Prophet's Hadith as a theoretical model applicable in madrasah education. This integration is crucial given the lack of previous studies analyzing the normative foundation of KBC from the Prophet's Hadith. The research method used is a literature review, collecting Hadith, scholarly articles, books, and Kemenag curriculum policy documents. Data were analyzed using content analysis and thematic hadith analysis to identify themes of love, compassion, ukhuwwah, and rahmah in the Prophet's Hadith. The results show that the Love-Based Curriculum has a strong foundation and aligns with the Prophet's Hadith teachings, encompassing five main topics: Love for Allah and His Messenger, Love for Knowledge, Love for the Environment, Love for Self and Fellow Human Beings, and Love for the Homeland. These Hadith provide a solid theological and normative foundation, such as prioritizing love for the Messenger over oneself and the obligation to seek knowledge. The contribution of this research lies in providing a robust operational and theoretical basis for madrasahs to use the Hadith as the main reference in formulating learning objectives, pedagogical strategies, and character evaluation within the KBC. This model has the potential to become a national standard for a more holistic, moderate, and transformative Islamic character education.